La obra musical de David Díaz Loyola y su aporte al desarrollo compositivo ecuatoriano de finales del siglo XX e inicios del siglo XXI. Análisis musical formal e interpretación de dos piezas para violonchelo y piano - Pauta Pauta, Janina Paulina (2023)
Ecuador has composers who have generally been little studied; such is the case of David Díaz Loyola, a composer who has a repertoire of academic and popular music for different formats. This curricular integration work aims to contribute to the dissemination of two musical pieces for cello and piano by David Díaz Loyola: “Krisdevals” and "Beyond the Mountains", which constitute the object of this study. The methodology is designed with a mixed approach which combinates quantitative and qualitative perspectives, accompanied by interviews, surveys, and study of documents. In the music field, formal analysis was applied, which allowed us to study the form, structure and compositional technique of the work, as important inputs to develop a correct interpretation. In the results of this research, it was identified that David Díaz Loyola shows trends between the avant-garde and nationalism, which are reflected in his compositional style. To conclude, by applying new compositional styles, the composer provides his repertoire with an important degree of technical complexity for interpretation. Keywords: nationalism, cello, music analysis, music interpretation.